Analyzing Institutional Models for Water Resources Management in Minas Gerais, Brazil - Theodoro, Hildelano Delanusse; Marques, Danilo (Sustainability in Debate, 2014)
The paper proposes to develop a critical analysis of the main institutional models of water management and how they were established over time by historical and environmental. Likewise, the legal basis exists for the development of public policies related to water theme is quoted in order to facilitate the understanding of the type of structure in the country for management. Be on your format bureaucratic, economic, financial or participatory, institutionalization Brazilian water resources currently aims to enable the interaction between their organizations toward a shared management of water, especially in a scenario of increasing participation and democratic decision-making processes.